Beyond Household Socioeconomic Status: Multilevel Modeling of Supply-Side Determinants of LPG Consumption among 5,500 Households in Sub- Saharan Africa - Shupler, Matthew; Mangeni, Judith; Tawiah, Theresa; Sang, Edna; Baame, Miranda; Anderson de Cuevas, Rachel; Nix, Emily; Betang, Emmanuel; Saah, Jason; Quansah, Reginald; Puzzolo, Elisa; Mbatchou, Bertrand; et al. (Research square, 2021)
Household transition to cleaner cooking fuels (e.g. liquefied petroleum gas (LPG)) has historically been understood as an “energy ladder” with clean energy access resulting from improvements in household socioeconomic status (SES). Recent studies have demonstrated the importance of supply-side determinants in increasing clean cooking, yet few large-scale studies have assessed their significance quantitatively. As part of the CLEAN-Air(Africa) study, a population-based survey was conducted (N = 5,638) assessing cooking practices in peri-urban communities within Cameroon, Kenya and Ghana. Multilevel logistic and log-linear regression were used to assess socioeconomic and supply-side determinants of LPG usage (primary versus secondary fuel) and consumption (kilograms/capita/year), respectively. Supply-side factors (e.g. cylinder refill and transportation costs) and using single versus multi-burner stoves were better predictors of both the probability of primarily cooking with LPG and annual LPG consumption than household SES. These results suggest the need for policies promoting LPG access and stove equipment that meet household needs.
Keywords: Clean cooking transitions; Primary fuel; Stove stacking; Liquefied petroleum gas; Cylinder refills